2016
DOI: 10.18034/mjmbr.v3i1.405
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Satisfaction with Public Health Care Services in Bangladesh: Some Critical Issues

Abstract: This paper attempts to explore the experiences of Bangladeshi patient with public health care services, clients self-perception of health, understanding their expectation and demands of health care towards government health practitioners and service providers. The study points out the issues and difficulties they faced in treatment or getting other services and presents some recommendations to improve the public hospital services.The study was undertaken using the interpretivist paradigm and based on qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…The present study extended the SERVQUAL model by adding 2 extra dimensions. Besides, these dimensions demonstrated significant validity and reliability coefficient scores in line with the study of Andaleeb and associates [11].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present study extended the SERVQUAL model by adding 2 extra dimensions. Besides, these dimensions demonstrated significant validity and reliability coefficient scores in line with the study of Andaleeb and associates [11].…”
Section: Discussionsupporting
confidence: 84%
“…Particularly, not-for-profit Non-Government Organizations (NGOs) provide rehabilitation services throughout Bangladesh [10]. Several studies have examined the healthcare sector of Bangladesh; they found that the patients are dissatisfied with the quality of healthcare services provided to them [10,11]. Accordingly, patients lost faith and participation in rehabilitation care, i.e.…”
mentioning
confidence: 99%
“…Many efforts can be made in improving the quality of health services, both from improving the quality of service personnel and aspects of facilities and the environment around health services. Thus, good quality health services can have an impact on a healthy and prosperous community [26], [27], [28], [29].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of services provided will certainly affect the feelings and satisfaction of patients [30], [31], aspects of the facility, and the environment around health services. Thus, good quality health services can have an impact on a healthy and prosperous community [26], [27], [28], [29].…”
Section: Discussionmentioning
confidence: 99%
“…ensuring health service delivery and access to skilled birth attendance, coverage of antenatal care and lack of trained physicians, nurses, pathologists, adequate number of hospital beds etc. which severely affect the satisfaction of patients including PWDs (BBS 2019;Hussain & Raihan, 2015;El Arifeen et al, 2013). They face additional health challenges with their physical impairments e.g.…”
Section: Exclusion From Health and Social Servicesmentioning
confidence: 99%